(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
This study investigated effect of virgin coconut oil (VCO)-derived fatty acids on the alteration of lipid profiles and liver tissues of high fat diet (HFD) fed mice. The initial fatty acids mixture was successfully obtained via hydrolysis process using Candida rugosa lipase (CRL). Enrichment of medium chain fatty acids (MCFA) from the initial fatty acid mixture using distillation process was developed to achieve 3 fractions of fatty acids mixture including Fraction I (MCFA mainly from C8 to C10), Fraction II of lauric acid (C12), and Fraction III (long chain fatty acids from C14 to C20). Among these agents, VCO only diminished ALT level but the initial FFA mixture decreased both ALT and AST levels compared with HFD-induced mice. Moreover, Fraction I and Fraction II showed an obvious difference in decreasing ALT, AST, total cholesterol, and LDL cholesterol levels as well as increasing HDL cholesterol level compared to other agents. It was observed a microvesicular steatosis and mild inflammation in liver section of mice fed with HFD whereas VCO, initial fatty acids, and Fraction II showed the beneficial effect on liver damage.